2013
DOI: 10.1097/sla.0b013e318288e957
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anemia Is an Independent Predictor of Postoperative Mortality and Adverse Cardiac Events in Elderly Patients Undergoing Elective Vascular Operations

Abstract: The presence and degree of preoperative anemia are independently associated with 30-day death and adverse cardiac events in patients 65 years or older undergoing elective open and endovascular procedures. Identification and treatment of anemia should be important components of preoperative care for patients undergoing vascular operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 26 publications
3
58
0
2
Order By: Relevance
“…A common challenge noted for acute events such as a fall or symptomatic infection is the frequent lack of sufficient information in clinical records on pre-existing factors that may have influenced susceptibility to a stressor that led to the event. Nevertheless, new methods such as natural language processing can capture clinical information in useful ways that will enhance the utility of clinical research to identify both exposures and outcomes (20).…”
Section: Uses Of Clinical Data In Predicting or Assessing Resiliencementioning
confidence: 99%
“…A common challenge noted for acute events such as a fall or symptomatic infection is the frequent lack of sufficient information in clinical records on pre-existing factors that may have influenced susceptibility to a stressor that led to the event. Nevertheless, new methods such as natural language processing can capture clinical information in useful ways that will enhance the utility of clinical research to identify both exposures and outcomes (20).…”
Section: Uses Of Clinical Data In Predicting or Assessing Resiliencementioning
confidence: 99%
“…These patients had multiple comorbidities and acquired coagulopathic disorders owing to major tissue trauma, CPB, large volume fluid resuscitation and antiplatelet/anticoagulant drug therapies. In previous reports, [1,[23][24][25] major bleeding and allogenic blood transfusions have been identified as strong predictors of poor clinical outcome. In the current study, fourfold-higher perioperative mortality was found in patients requiring five PRBC or more compared with those requiring <5 units, although both groups presented similar clinical characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, intraoperative transfusion is associated with an increased risk of 30-day postoperative mortality for elderly patients undergoing noncardiac surgery with preoperative hematocrit levels between 30 and 35.9 % and [500 mL of intraoperative blood loss. However, transfusion is particularly harmful in patients without postoperative anemia (hemoglobin C 9.0 g/dL), with a fourfold increased risk of 30-day death [4]. In addition, patients receiving a postoperative transfusion also have significantly increased risks for 30-day mortality and morbidity, and infectious complications after noncardiac surgery [5].…”
Section: Dear Editormentioning
confidence: 99%